Peningkatan Kemampuan Berpikir Kritis Siswa Biologi Dengan Menggunakan Model PjBL Berbasis STEM ( Science,Technology, Engineering, Mathematics): (Improving Critical Thinking Ability of Biology Students with STEM-Based PjBL Model (Science Technology, Engineering, Mathematics)) - Wandari, Welli; Nursamsu, Nursamsu; Wahyuni , Ayu (Program Studi Pendidikan Biologi FKIP Universitas Jambi, 2024)
STEM-based Project Based Learning model is a learning model that emphasizes students to complete a project in groups where the project integrates science, technology, engineering, and mathematics. This study aims to determine the effect of PjBL (Project Based Learning) model based on STEM (Science, Technology, Engineering, Mathematics) to improve critical thinking skills of biology students of SMAN 3 Langsa. This study uses a type of quantitative research with a quasy experimental method with a pretest-posttest control group design using two sample classes, namely the experimental class and the control class. The samples in this study amounted to 36 experimental class students and 36 control class students. The results of the research instrument trial showed that the average value of the experimental class pretest was 40.11 (low) and the control class was 38.65 (low) so that the difference between the two classes was 1.46. While the average posttest value of the experimental class was 81.40 (high) and the control was 72.42 (medium) so that the difference between the two classes was 8.98. With the hypothesis test value titung>ttabel or 5.59>1.6669. So it can be concluded that Ha is accepted and H0 is rejected, meaning that there is a significant influence in using the STEM-based PjBL model (Science, Technology, Engineering, Mathematics) to improve students' critical thinking skills at SMAN 3 Langsa. While the experimental class N-gain test results of 0.65 (medium category) were higher than the control class of 0.49 (medium category). Absrtak. Model Project Based Learning berbasis STEM adalah suatu model pembelajaran yang lebih menekankan siswa untuk menyelesaikan suatu proyek secara berkelompok dimana proyek tersebut mengintegrasikan sains, teknologi, teknik, dan matematika. Penelitian ini bertujuan untuk mengetahui pengaruh model Project Based Learning (PjBL) berbasis Science, Technology, Engineering, Mathematics (STEM) untuk meningkatkan kemampuan berpikir kritis siswa biologi di SMAN 3 Langsa. Penelitian ini menggunakan jenis penelitian kuantitatif dengan metode quasy eksperimen dengan rancangan pretest-posttest control group design dengan menggunakan dua kelas sampel, yaitu kelas eksperimen dan kontrol. Sampel dalam penelitian berjumlah 36 siswa kelas eksperimen dan 36 siswa kelas kontrol. Hasil penelitian instrumen tes menunjukkan bahwa adanya nilai rata-rata pretest kelas eksperimen sebesar 40.11 (rendah) dan kelas kontrol sebesar 38,65 (rendah) sehingga selisih antara kedua kelas tersebut sebesar 1,46 Sedangkan nilai rata-rata posttest kelas eksperimen sebesar 81,40 (tinggi) dan kontrol sebesar 72,42 (sedang) sehingga selisih antara kedua kelas tersebut sebesar 8,98. Dengan nilai uji hipotesis thitung>ttabel atau 5,59 >1,6669. Sehingga dapat disimpulkan bahwa Ha diterima dan H0 ditolak, artinya terdapat pengaruh yang signifikan dalam menggunakan model PjBL berbasis Science, Technology, Engineering, Mathematics (STEM) untuk meningkatkan kemampuan berpikir kritis siswa di SMAN 3 Langsa. Sedangkan hasil uji N-gain kelas eksperimen sebesar 0,65 (kategori sedang) lebih tinggi dari pada kelas kontrol sebesar 0,49 (kategori sedang).